17q21 gene variation is not associated with asthma in adulthood. Issue 1 (January 2015) - Kreiner‐Møller, E.; Strachan, D. P.; Linneberg, A.; Husemoen, L. L. N.; Bisgaard, H.; Bønnelykke, K.
Abstract Background 17q21 gene variants are the strongest known genetic determinants for childhood asthma and have been reported to interact with environmental tobacco smoke exposure in childhood. It remains unclear whether individuals with 17q21 risk variants have increased risk of asthma or reduced lung function in adulthood. The aim was to examine the association between the 17q21 region and current adult asthma and lung function, and interaction with active smoking. Methods We investigated the single nucleotide polymorphism rs7216389 at the 17q21 locus in 3471 adults from the Health2006 cross‐sectional study and in 7008 adults from The British 1958 Birth Cohort and examined the association with current asthma, spirometry measures, and related atopic traits. Analyses were performed for interaction with active smoking. Results We found no association between rs7216389[T] and asthma when meta‐analyzed (OR = 1.02 [0.92–1.13], P = 0.81). The risk variant was associated with reduced FEV1 as compared to normal FEV1 (OR = 1.10 [1.01–1.12], P = 0.033) and with allergic sensitization (OR = 1.10 [1.03–1.17], P = 0.003). Individuals with rs7216389 risk variants smoked as frequently as individuals without risk variants, and there was no evidence that smoking modified the association between rs7216389 and asthma. Conclusion Our study suggests that the 17q21 rs7216389 locus variant does not substantially influence asthma risk in adulthood or susceptibility to detrimental effects of active smoking. This contrasts the findings in children and suggests that this locus is associated with a childhood‐specific asthma endotype.